Decision Support System for Thesis Session Pass Recommendation Using AHP (Analytic Hierarchy Process) Method - Valentino, V. H.; Setiawan, Heri Satria; Saputra, Aswin; Haryanto, Yuli; Putra, Arman Syah (CV. Inara, 2021)
AbstractThe background this time is how the scoring system is still objective in the thesis trial system, therefore withthis decision support system, the objective assessment will become a definite scoring system, and will beable to help examiners provide the best advice to take. decisions to be taken during the student thesis trial.The method used in this research is to use quantitative methods, by conducting a librarian study and thencombined with data taken from student participants in the thesis examination, with the library studymethod, it will be possible to explore this research and data processing will also be maximized. Manysystems use the AHP algorithm method to make decisions that are difficult to make, using the AHP methodcan be taken into consideration in making decisions, because data processing using the AHP method willprovide the best advice for making an important decision. This research will produce a system proposal andhow the data is obtained, then how the data is processed to produce a system proposal, which is best formaking decisions about students who are currently passing their thesis exams or not, with the proposedsystem will greatly help the examiner take decisions that were previously objective.Keywords: Decision Support System, Thesis Session, Pass, AHP.